Substrate mediated nitridation of niobium into superconducting Nb(2)N thin films for phase slip study - Gajar, Bikash (Sci Rep, 2019)
Here we report a novel nitridation technique for transforming niobium into hexagonal Nb(2)N which appears to be superconducting below 1K. The nitridation is achieved by high temperature annealing of Nb films grown on Si(3)N(4)/Si (100) substrate under high vacuum. The structural characterization directs the formation of a majority Nb(2)N phase while the morphology shows granular nature of the films. The temperature dependent resistance measurements reveal a wide metal-to-superconductor transition featuring two distinct transition regions. The region close to the normal state varies strongly with the film thickness, whereas, the second region in the vicinity of the superconducting state remains almost unaltered but exhibiting resistive tailing. The current-voltage characteristics also display wide transition embedded with intermediate resistive states originated by phase slip lines. The transition width in current and the number of resistive steps depend on film thickness and they both increase with decrease in thickness. The broadening in transition width is explained by progressive establishment of superconductivity through proximity coupled superconducting nano-grains while finite size effects and quantum fluctuation may lead to the resistive tailing. Finally, by comparing with Nb control samples, we emphasize that Nb(2)N offers unconventional superconductivity with promises in the field of phase slip based device applications.